Transmission and impact of stock market shocks on the world economy - Luccas Assis Attílio (Central Bank Review (CBR), 2024)
In this study, we examine stock market shocks using a Global Vector Autoregressive (GVAR) model encompassing 26 countries from January 1999 to June 2022. Our findings reveal that i) shocks originating from advanced economies (AD) exhibit greater persistence in generating fluctuations compared to shocks from emerging market economies (EME); ii) negative stock market shocks are associated with devaluations of domestic currencies, endogenous responses of monetary policy, and global recession. Our estimates suggest that stock market fluctuations have significant potential to destabilize international markets, with contagion spreading rapidly. Our approach contributes to existing literature by constructing a comprehensive model of the world economy, simulating aggregate shocks, and assessing the relevance of global shocks based on the level of economic development.
Keywords: G17; E32; E44; F37; 330; Stock market; Fluctuation; Emerging economies; Advanced economies; Bilateral trade